The Predictive Role of CD40L in The Development of Abdominal Aortic Aneurysms in A Murine Model: A Pilot Study - Patelis, Nikolaos; Moris, Dimitrios; Davakis, Spyridon; Bakoyiannis, Chris; Liakakos, Theodore; Georgopoulos, Sotirios (Cardiology and Cardiovascular Medicine, 2019)
The mechanism behind the incidence and the development of infrarenal aortic aneurysm and the factors affecting the rate of aortic dilatation remain largely unknown. The need for a biomarker capable to facilitate the diagnosis and the timed repair of an aortic aneurysm could reduce overall mortality. The aim of this study is to report on the potential predictive role of CD40L in aortic diameter growth and the development of AAA. The study group of 16 Wistar rats underwent a laparotomy and an infusion of porcine pancreatic elastase of the infrarenal aorta under hydrostatic pressure. The control group (n=16) underwent a sham procedure. At an interval of seven days, the animals of both groups underwent a laparotomy and the aortic dimension was measured. Blood samples were obtained at the same intervals. No significant change of the animals’ weight was recorded. AAA was formed in all animals and aortic diameters differed significantly between the two groups. After the intervention, CD40L demonstrated a gradual increase in the study group and CD40L serum levels in this group were significantly higher compared to the control group; in parallel with the trend of aortic dilatation. CD40L could potentially act as biomarkers of the presence and development of infrarenal aortic aneurysms, but further studies with a larger number of animals are necessary.